Platformization and sustainability - potential and challenges of platform business models for entrepreneurs - Grassow, Julia Christin (2022)
The shift to a sustainable economy implies a radical transformation of businesses and society. This paper investigates whether increasing platformization can accelerate the sustainability transition by outlining the potentials and challenges of platform business models from a consumer and business lens. The research first examines the power of platforms to influence sustainable consumption patterns based on a quantitative survey. Moreover, a multiple-case study is conducted to explorehow entrepreneurs can leverage sustainability-oriented platform business models to seize competitive advantage. The results contribute to a better understanding of sustainable platform usage and offer entrepreneurial strategies for sustainable business.